Emergency general surgery transfer to lower acuity facility: The role of right-sizing care in emergency general surgery regionalization. Issue 1 (January 2022) - Baimas-George, Maria; Schiffern, Lynnette; Yang, Hongmei; Paton, Lauren; Barbat, Selwan; Matthews, Brent; Reinke, Caroline E.
Abstract : BACKGROUND: Regionalization of emergency general surgery (EGS) has primarily focused on expediting care of high acuity patients through interfacility transfers. In contrast, triaging low-risk patients to a nondesignated trauma facility has not been evaluated. This study evaluates a 16-month experience of a five-surgeon team triaging EGS patients at a tertiary care, Level I trauma center (TC) to an affiliated community hospital 1.3 miles away. METHODS: All EGS patients who presented to the Level I TC emergency department from January 2020 to April 2021 were analyzed. Patients were screened by EGS surgeons covering both facilities for transfer appropriateness including hemodynamics, resource need, and comorbidities. Patients were retrospectively evaluated for disposition, diagnosis, comorbidities, length of stay, surgical intervention, and 30-day mortality and readmission. RESULTS: Of 987 patients reviewed, 31.5% were transferred to the affiliated community hospital, 16.1% were discharged home from the emergency department, and 52.4% were admitted to the Level I TC. Common diagnoses were biliary disease (16.8%), bowel obstruction (15.7%), and appendicitis (14.3%). Compared with Level I TC admissions, Charlson Comorbidity Index was lower (1.89 vs. 4.45, p < 0.001) and length of stay was shorter (2.23 days vs. 5.49 days, p < 0.001) for transfers. Transfers had a higher rate of surgery (67.5% vs. 50.1%, p < 0.001) and lower readmission and mortality (8.4% vs. 15.3%, p = 0.004; 0.6% vs. 5.0%, p < 0.001). Reasons not to transfer were emergency evaluation, comorbidity burden, operating room availability, and established care. No transfers required transfer back to higher care (under-triage). Bed days saved at the Level I TC were 693 (591 inpatients). Total operating room minutes saved were 24, 008 (16, 919, between 7:00 AM and 5:00 PM). CONCLUSION: Transfer of appropriate patients maintains high quality care and outcomes, while improving operating room and bed capacity and resource utilization at a tertiary care, Level I TC. Emergency general surgery regionalization should consider triage of both high-risk and low-risk patients. LEVEL OF EVIDENCE: Prospective comparative cohort study, Level II. Abstract : Safe triage of low-risk EGS patients from tertiary centers to lower-level centers does not sacrifice outcomes of care, preserving resources at tertiary care hospitals.